2004
DOI: 10.1093/toxsci/kfh115
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Potential of Triethanolamine to Alter Hepatic Choline Levels in Female B6C3F1 Mice

Abstract: Triethanolamine (TEA), a widely used nongenotoxic alcohol-amine, has recently been reported to cause an increased incidence of liver tumors in female B6C3F1 mice, but not in males nor in Fischer 344 rats. Choline deficiency induces liver cancer in rodents, and TEA could compete with choline uptake into tissues. The potential of TEA to cause choline deficiency in the liver of these mice as a mode of tumorigenesis was investigated. Groups of female B6C3F1 mice were administered 0 (vehicle) or a maximum tolerated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…Manufacturers sometimes substitute triethanolamine (TEA) for DEA in products. We found that TEA can also perturb choline metabolism (37), and suggest that it, too, should be evaluated for effects on pregnancy and brain development.…”
Section: Discussionmentioning
confidence: 74%
“…Manufacturers sometimes substitute triethanolamine (TEA) for DEA in products. We found that TEA can also perturb choline metabolism (37), and suggest that it, too, should be evaluated for effects on pregnancy and brain development.…”
Section: Discussionmentioning
confidence: 74%
“…Previous evaluations of NDELA formation in vivo indicated maximal formation at approximately 2 h post dosing (Stott et al, 2000b). As shown in Table 3, the concentration of NDELA in the blood and ingesta of TEA-treated mice averaged 0.001 § 0.0005 g/g (<detection limit in most samples) and 0.044 § 0.059 g/g, respectively.…”
Section: In Vivo Experimentsmentioning
confidence: 83%
“…However, a recent dermal (skin paint) oncogenicity study of TEA conducted by the NTP (2003) in B6C3F1 mice at dose levels up to 2000 mg/kg/day in males and at 100, 300, and 1000 mg/kg/day in females for 2 years revealed an increased incidence of liver adenomas in females (only) at all three dose levels. The mode of action (MoA) for liver tumour formation in female B6C3F1 mice has been reported to be related to TEA-induced depletion of choline (Stott et al, 2004), a non-genotoxic threshold-based MoA. However, the frequent suggestion in the literature of in vivo formation of the nitrosamine N-nitrosodiethanolamine (NDELA) from TEA had also raised the question of the potential involvement of this, more serious, MoA in liver tumour formation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that choline deficiency induces liver cancer in rodents 51,52 ; therefore, the potential of TEA to cause choline deficiency in the liver of female B6C3F 1 mice was investigated as a mode of tumorigenesis. 53 Female mice were dosed dermally with unoccluded applications of 10, 100, 300, or 1000 mg/kg/d TEA in acetone, 5 d/wk for 3 weeks, and female CDF rats were dosed in a similar manner with 250 mg/kg/d TEA. (Purity of TEA was 99+%; diethanolamine impurity levels were 0.04% and 0.45%.)…”
Section: Carcinogenicitymentioning
confidence: 99%